Economics made easy a quick guide to mirco and macro economics - Ng, David S. H. (Kumpulan Budiman, 2001)
Economy Made Easy provides the foundation and essential review of economics theory. It discusses the concept in an easy to understand manner. Technical jargons are kept to a minimal. As such it is a useful guide for students who are in a rush for time.